2020
DOI: 10.1016/j.isci.2020.101600
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloprotease-7 Mediates Nucleolar Assembly and Intra-nucleolar Cleaving p53 in Gefitinib-Resistant Cancer Stem Cells

Abstract: Summary The enlarged distinct bulky-ball-like nucleolus matrix assembly is observed in most cancer stem cells (CSCs); however, the underlying mechanism is largely unknown. We show that matrix metalloproteinase-7 (MMP-7) shedding MUC-1 SEA domain releases MUC-1 C-ter, facilitating the nucleolus trafficking of p53 in gefitinib-resistant lung CSCs. The nucleolus colocalizations of p53, MUC-1 C-ter, MMP-7 and nucleolin were observed in the CD34 + CXADR + CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…A few research groups, including us, observed that salinomycin itself or by sensitizing chemodrugs or radiation, moderately or strongly increases DNA damage, inducing G2 arrest and reduction of p21 protein level in cancer cells 45,46,70–72 . In accord with these findings, we also further noticed the phosphorylation of tripartite motif‐containing 28 (TRIM28) along with salinomycin treatment in neuroblastoma cells (unpublished data).…”
Section: Multifunctional Mechanisms Of Salinomycin Against Cscsupporting
confidence: 77%
See 1 more Smart Citation
“…A few research groups, including us, observed that salinomycin itself or by sensitizing chemodrugs or radiation, moderately or strongly increases DNA damage, inducing G2 arrest and reduction of p21 protein level in cancer cells 45,46,70–72 . In accord with these findings, we also further noticed the phosphorylation of tripartite motif‐containing 28 (TRIM28) along with salinomycin treatment in neuroblastoma cells (unpublished data).…”
Section: Multifunctional Mechanisms Of Salinomycin Against Cscsupporting
confidence: 77%
“…Studies from us and also other groups have shown that salinomycin suppresses CSCs in many cancer types including breast cancer, 24 , 34 , 44 , 75 , 91 , 92 , 93 , 94 neuroblastoma, 51 GBM, 38 , 43 , 76 , 95 medulloblastoma, 71 pancreatic cancer, 20 , 37 , 96 colon cancer, 67 , 82 , 97 , 98 , 99 prostate cancer, 100 , 101 , 102 melanoma, 103 lung cancer, 72 , 104 and so on. Despite the above‐mentioned efforts, the cellular target of salinomycin remained unclear for a long time.…”
Section: Multifunctional Mechanisms Of Salinomycin Against Cscmentioning
confidence: 99%
“…However, members of the transmembrane mucins play opposite roles in drug resistance and tumor progression. Studies have shown that MUCs has a regulatory effect on EGFR 55 , 56 . The SEA domain of MUCs in drug-resistant cells were shed under the action of matrix metalloproteinase-7 (MMP-7), releasing MUC1-C-ter and promoting the nucleolus transport of p53 in gefitinib-resistant cells 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MUCs has a regulatory effect on EGFR 55 , 56 . The SEA domain of MUCs in drug-resistant cells were shed under the action of matrix metalloproteinase-7 (MMP-7), releasing MUC1-C-ter and promoting the nucleolus transport of p53 in gefitinib-resistant cells 55 . Here, we demonstrated a more complicated epigenetic regulation of MUC17 in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Drugs targeting NCL, such as salinomycin, can effectively kill CSCs, which is important for cancer drug-resistance therapy and prognosis. [17] The biological function of NCL in promoting cellular homeostasis is also responsible for the development of its malignant features under pathological conditions.…”
Section: Introductionmentioning
confidence: 99%